The Acquisition of Indigenous Plasmids by a Genetically Marked Pseudomonad Population Colonizing the Sugar Beet Phytosphere Is Related to Local Environmental Conditions - Lilley, A. K. (1997)
The transfer of naturally occurring conjugative plasmids from the indigenous microflora to a genetically modified population of bacteria colonizing the phytospheres of plants has been observed. The marked strain (Pseudomonas fluorescens SBW25EeZY6KX) was introduced as a seed dressing to sugar beets (Beta vulgaris var. Amethyst) as part of a field experiment to assess the ecology and genetic stability of deliberately released bacterial inocula. The sustained populations of the introduced strain, which colonized the phytosphere, were assessed throughout the growing season for the acquisition of plasmids conferring mercury resistance (Hg(supr)). Transconjugants were isolated only from root and leaf samples collected within a narrow temporal window coincident with the midseason maturation of the crop. Conjugal-transfer events were recorded during this defined period in two separate field release experiments conducted over consecutive years. On one occasion seven of nine individual plants sampled supported transconjugant P. fluorescens SBW25EeZY6KX, demonstrating that conjugative gene transfer between bacterial populations in the phytosphere may be a common event under specific environmental conditions. The plasmids acquired in situ by the colonizing inocula were identified as natural variants of restriction digest pattern group I, III, or IV plasmids from five genetically distinct groups of large, conjugative mercury resistance plasmids known to persist in the phytospheres of sugar beets at the field site. These data demonstrate not only that gene transfer may be a common event but also that the genetic and phenotypic stability of inocula released into the natural environment cannot be predicted.